Perancangan User Experience Aplikasi Pembelajaran & Pengembangan Minat pada Esport menggunakan Metode Human Centered Design (Studi Kasus: Gamers Casual-Competitive FILKOM UB) - Wahyu Rafi' Adi Wicaksono; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Esports is one of the growing industries in the digital era. In Indonesia, esports is one of the most popular by gamers. The structure of the esports ecosystem is a potential and opportunity to create professional players in their fields, therefore it is necessary to have a learning media that equips gamers who want to become professional players or esport athletes. This research resulted in designing a user experience application for learning & developing interest in esports in the Faculty of Computer Science, Universitas Brawijaya with the typology of Gamers Casual-Competitive. The design method used is Human Centered Design and carried out usability testing using a task scenario and a System Usability Scale. The test results from the application design obtained an effectiveness value of 95% on mentor display and 89% on gamer display. The efficiency value is 0.151 goals/second for mentor display and 0.205 goals/second for gamers. Mentor satisfaction value on the display is 88 which is included in the